A6_1 Sea Titans - Gorringe, Peter; Pizarro Salcedo, Claudio; Price, Tom; Bristowe, Thomas (Physics Special Topics, 2021)
During WWII, two of the largest Naval powers in the world, the USA and Japan, raced to create the most powerful ships ever seen. This goal was represented by the two famous battleships USS Missouri and IJN Yamato for the USA and Japan respectively. In this paper, we estimate the penetration power of USS Missouri and IJN Yamato’s Main Battery Guns. By comparing these values to the known belt armour schemes of both ships, at ∼ 20km, we determine that USS Missouri has ∼ 0.335m of penetration; IJN Yamato has ∼ 0.392m of penetration. This means that at this distance, IJN Yamato has a distinct tactical advantage, under the assumptions of our system.